Hydrazine-Fueled Solution Combustion Method: Fuel/Oxidizer Ratio Effects on Photocatalytic Performance of Bismuth Oxide - Yayuk Astuti; Trie Nanda Mulyana; Brainy Happy Ana Tasiman; Adi Darmawan; Hendri Widyandari (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
Bismuth oxide nanoparticles were synthesized through the solution combustion method with a variation of fuel: oxidizer (hydrazine: bismuth nitrate) ratios (ϕ) of ϕ<1, ϕ=1 (stoichiometrically balanced) and ϕ> 1. Bismuth oxide nanoparticles were characterized by Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), and UV-Visible Diffuse Reflectance Spectroscopy (UV-DRS). The FTIR spectra obtained implies that the bismuth oxide nanoparticles of the three ratios contain Bi-O-Bi and Bi-O groups indicating its successful formation. XRD diffractogram suggests that the synthesized bismuth oxide nanoparticles form the α-Bi2O3 crystalline phase for ϕ<1 and ϕ>1; meanwhile a mixture of α-/β- Bi2O3 phases for ϕ=1. The SEM image illustrates that bismuth oxide nanoparticles form pebble shapes with the ratios in the order of increasing particle sizes of ϕ>1, ϕ=1, and ϕ<1. The UV-DRS results show that the bismuth oxide with ϕ<1, ϕ=1, and ϕ>1 have respective band gap energies of 2.76 eV, 2.72 eV, and 2.78 eV. The evaluation of the photocatalytic activity of the three bismuth oxide samples shows bismuth oxide with ϕ=1 has the highest photocatalytic activity in remazol black B and methyl orange dyes with rate constants 6.744 x 10-5 s-1 and 7.369 x 10-5 s-1, respectively. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).